Erbin and ErbB2 play roles in the sexual differentiation of the song system nucleus HVC in bengalese finches (Lonchura Striata var. domestica). Issue 1 (17th November 2017) - Zhao, Yueliu; Zhang, Xuebo; Wang, Rui; Bing, Jie; Wu, Fan; Zhang, Yitong; Xu, Jincao; Han, Zhongming; Zhang, Xinwen; Zeng, Shaoju
ABSTRACT: Song control nuclei have distinct sexual differences in songbirds. However, the mechanism that underlies the sexual differentiation of song nuclei is still not well understood. Using a combination of anatomical, pharmacological, genetic, and behavioral approaches, the present study investigated the role of erbb2 (a homolog of the avian erythroblastic leukemia viral oncogene homolog 2) and the erbb2 ‐interacting gene, erbin, in the sexual differentiation of the song nucleus HVC in the Bengalese finch. We first found that both erbin and erbb2 were expressed in the developing HVC at posthatch day (PHD) 15 in a male‐biased fashion using qRT‐PCR and in situ hybridization. Following the addition of a pharmaceutical inhibitor of the ErbB2 signaling pathway to the culture medium, cell proliferation in the cultured ventricle zone (VZ) that overlies the developing HVC decreased significantly. After the injection of erbin ‐ or erbb2 ‐interfering lentiviruses into the HVC and its overlying VZ at PHD 15, the cell proliferation in the VZ at PHD 24, the number of the differentiated neurons (Hu + /BrdU + or NeuN + /BrdU + ) in the HVC at PHD 31 or PHD 130, and the number of RA‐projecting cells at PHD 130 all decreased significantly. Additionally, the adult songs displayed serious abnormalities. Finally, 173 male‐biased genes were expressed in the developing HVC at PHD 15 using cDNA microarrays, of which 27.2% were Z‐linked genes and approximately 20 genes were involved in the Erbin‐ or ErbB2‐related signaling pathways. Our results provide some specific genetic factors that contribute to neurogenesis and sex differentiation in a song nucleus of songbirds. © 2017 Wiley Periodicals, Inc. Develop Neurobiol 78: 15–38, 2018